2018
DOI: 10.1093/ajcn/nqx070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Mediterranean diet on cognition and brain morphology and function: a systematic review of randomized controlled trials

Abstract: Five RCTs of the Mediterranean diet and cognition have been published to date. The data are mostly nonsignificant, with small ESs. However, the significant improvements in cognitive domain composites in the most robustly designed study warrant additional research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 84 publications
7
76
2
2
Order By: Relevance
“…Several randomized controlled trials (RCTs) have examined the association between MedDi and cognitive function [33][34][35]. The Spanish PREDIMED (Prevención con Dieta Mediterranea) study was the cornerstone trial showing that patients at high cardiovascular risk consuming MedDi (supplemented with either extra-virgin olive oil or nuts) had a reduced incidence of cardiovascular events compared to those following a low-fat diet after a follow-up period of five years [36,37].…”
Section: Mediterranean Dietmentioning
confidence: 99%
“…Several randomized controlled trials (RCTs) have examined the association between MedDi and cognitive function [33][34][35]. The Spanish PREDIMED (Prevención con Dieta Mediterranea) study was the cornerstone trial showing that patients at high cardiovascular risk consuming MedDi (supplemented with either extra-virgin olive oil or nuts) had a reduced incidence of cardiovascular events compared to those following a low-fat diet after a follow-up period of five years [36,37].…”
Section: Mediterranean Dietmentioning
confidence: 99%
“…As an indicator of therapeutic validity, the quality of the intervention utilised in the studies was also assessed. The areas of interest were informed by an earlier review (38) and included whether (i) a dietitian was involved in the design of the dietary intervention; (ii) the dietary intervention was a partial or full simulation of the low-inflammatory diet; (iii) there was the monitoring of adherence to the dietary intervention and (iv) a validated tool was utilised to measure dietary adherence.…”
Section: Risk Of Bias In Individual Studiesmentioning
confidence: 99%
“…For example, the PREDIMED programme provided both individual (with a dietitian) and group support for participants approximately every 3 months, meaning between 12 and 26 sessions of each depending on the overall study length, and this robust design may have contributed in part to the success of the programme (Radd‐Vagenas et al . ).…”
Section: Future Directions and Medex‐ukmentioning
confidence: 97%
“…A recent systematic review, however, identified five separate RCTs on the effects of a MDP on cognition, including five specific sub-studies from PREDIMED RCT (only two of which were reported by SACN; Radd-Vagenas et al 2018). The authors note that only eight of the 66 cognitive outcomes measured within these studies indicated that Mediterranean diet was associated with better cognitive performance, with effect sizes ranging from small (0.32) to large (1.66).…”
Section: Heart Health and Cognitive Healthmentioning
confidence: 99%